Political violence and progressive academics: Manganyi, NC & du Toit (eds) (1990) Political violence and the struggle in South Africa. Johannesburg: Southern Book Publishers. - Marais, Etienne (PINS-Psychology in Society, 2026)
Political violence and the struggle In South Africa (hereafter PVSA) was initiated by the "Political violence and health resources project" at Wits who brought together a number of psychologists and academics interested in other areas criminology, law, anthropology, media studies, sociology, philosophy and human rights. PVSA is a collection of thirteen essays reflecting on academic and professional discourses during the "time of the comrades" - from about 1984 to 1988. The binding theme is "the personal and professional involvement" of the contributors. The focus is not so much on political violence itself, but rather the way it is understood, analysed, and indeed, legitimised through various professional and academic discourses.